Synthesis and evaluation of a novel monomeric amine as sodium montmorillonite swelling inhibitor - Weichao Du; Xiaolin Pu; Jinsheng Sun; Xiao Luo; Yanna Zhang; Lu Li (Adsorption Science & Technology)
A novel monomeric amine sodium montmorillonite swelling inhibitor: N 1 , N 2 -ditetradecy- N 1 , N 1 , N 2 , N 2 -tetrakis (2-hydroxyethyl) ethane-1,2-diaminium bromide was obtained from diethanolamine, 1-bromotetradecane, and 1, 2-dibromoethane. N 1 , N 2 -ditetradecy- N 1 , N 1 , N 2 , N 2 -tetrakis (2-hydroxyethyl) ethane-1,2-diaminium bromide was characterized by means of Fourier transform infrared, 1 H NMR spectroscopy, elemental analysis, linear swelling tests, particle size distribution tests, X-ray diffraction, and thermogravimetric. Linear swelling tests showed that the swelling height of sodium montmorillonite in 1.0 wt% N 1 , N 2 -ditetradecy- N 1 , N 1 , N 2 , N 2 -tetrakis (2-hydroxyethyl) ethane-1,2-diaminium bromide solution was only 2.0 mm after 16 h (fresh water was 5.0 mm). Particle size distribution tests exhibited that the median diameter and mean particle size of sodium montmorillonite in 1.0 wt% N 1 , N 2 -ditetradecy- N 1 , N 1 , N 2 , N 2 -tetrakis (2-hydroxyethyl) ethane-1,2-diaminium bromide solution obviously increased to 16.1 and 85.4 µm, respectively (fresh water was 8.1 and 21.8 µm). In thermogravimetric tests, in comparison with pure sodium montmorillonite, the decrease of water content in sodium montmorillonite/ N 1 , N 2 -ditetradecy- N 1 , N 1 , N 2 , N 2 -tetrakis (2-hydroxyethyl) ethane-1,2-diaminium bromide indicated N 1 , N 2 -ditetradecy- N 1 , N 1 , N 2 , N 2 -tetrakis (2-hydroxyethyl) ethane-1,2-diaminium bromide expelled the water molecules out of the interlayer, which was beneficial to wellbore stability. Fourier transform infrared spectra of certain concentration N 1 , N 2 -ditetradecy- N 1 , N 1 , N 2 , N 2 -tetrakis (2-hydroxyethyl) ethane-1,2-diaminium bromide/sodium montmorillonite indicated the successful physical adsorption and interaction between N 1 , N 2 -ditetradecy- N 1 , N 1 , N 2 , N 2 -tetrakis (2-hydroxyethyl) ethane-1,2-diaminium bromide with sodium montmorillonite. In addition, the results of X-ray diffraction tests showed the obtained 1.0 wt% N 1 , N 2 -ditetradecy- N 1 , N 1 , N 2 , N 2 -tetrakis (2-hydroxyethyl) ethane-1,2-diaminium bromide solution could remarkably reduce the interlayer distance of wet sodium montmorillonite (from 1.94 to 1.37 nm).